Treatment of Inflammatory Bowel Disease in Children - D Grant Gall (Canadian Journal of Gastroenterology)
As no curative therapy exists, supportive measures play an important role in the management of patients with inflammatory bowel disease (IBO). Aminosalicylic acid (ASA) compounds and corticosteroids remain the mainstay of medical therapy. Aminosalicylates are recommended for therapy of mild to moderate active ulcerative colitis and for the maintenance of remission in ulcerative colitis. The role of 5-ASA preparations in Crohn's disease is less clear. In granulomatous colitis, 5-ASA therapy is recommended. With the development of new delivery systems, the role for 5-ASA in the treatment of small bowel Crohn's disease is under investigation. Prednisone remains the drug of choice in severe ulcerative colitis and active Crohn's disease. The role of immunosuppressive drugs in pediatric patients is unclear. Nutritional therapy has been an important advance in the treatment of children with Crohn's disease, especially those with growth failure. Nutritional therapy can consist of combined total parenteral and enteral nutrition or enteral nutrition alone. An initial period of total parenteral nutrition followed by a six to eight week course of enteral therapy with a semisynthetic diet has been shown to be effective in the management of patients with severe active disease and growth failure.